Food Security and Biofuels in Latin America and the Caribbean Region: A Data Panel Analysis on Eight Countries - Maria Lourdes Ordoñez Olivo; Zoltán Lakner (Energies, 2023)
In the short, medium, and long term, a sustainable bioeconomy can help address one of the main concerns of most countries concerning the food crisis, particularly in the Latin American and Caribbean contexts, where food security and the bioeconomy are crucial for the region’s development and sustainability. However, to avoid negative impacts on the environment and food production, all sectors of the bioeconomy, especially those related to biofuel production, must be sustainable and environmentally conscious. This study analyses historical correlations between three dependent variables related to basic concepts of food security and independent variables framed by biofuel production through a panel data study in eight Latin American and Caribbean countries between 2007 and 2021. Of the three econometric models analyzed, two are statistically significant. The first shows a positive correlation between biofuel production and the food production index. The third shows a negative correlation between the percentage of undernourished people and biofuel production. In conclusion, according to the historical data evaluated in the countries studied, the impact of biofuel production on the food security variables analyzed is positive. This positive relationship can be interpreted as an opportunity for the region’s countries to generate additional bio-economic income, taking advantage of the region’s potential and providing new opportunities for producers, especially in rural areas.